The schema therapy clinician's guide : a complete resource for building and delivering individual, group and integrated schema mode treatment programs - Farrell, Joan M.; Reiss, Neele; Shaw, Ida A. (Chichester, West Sussex : Wiley Blackwell, 2014)
The Schema Therapy Clinician's Guide is a complete clinical resource for psychotherapists looking to implement Schema Therapy, Group Schema Therapy, or a combination of both in a structured, cost-effective way. Written by world leaders in the field, including the creators of Group Schema Therapy, this book is based on the only model for integrated, time-limited Schema Therapy that has been proven in research studies. Accessible for Schema Therapy beginners, the book will also be invaluable for group or individual therapists interested in combining the two approaches, and for clinicians seeking ready-made resources for work on specific schema modes.
The authors provide ready-to-use individual and group sessions with patient handouts, independently effective but also linked by schema mode that can be delivered across a range of treatment lengths. It divides the work of Schema Therapy into its basic components of cognitive, experiential, and behavioral pattern-breaking work, focusing on one of these components at a time in sessions. Readers can thus select the formats and modes that are most appropriate for the needs of their own patient group and then use those sessions as a basis for planning and delivering a treatment program. Ways to balance individual and group focus are discussed throughout. --Book Jacket.
Schema therapy basics -- Treatment program specifics -- The group schema therapy sessions -- The individual schema therapy sessions -- Training, supervision, research and concluding remarks.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Psychotherapy -- Handbooks, manuals, etc; Schema-focused cognitive therapy -- Handbooks, manuals, etc; Psychotherapy -- methods; Personality Disorders -- therapy; Psychotherapy, Group -- methods; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Psychotherapy; Schema-focused cognitive therapy; Handbooks; Electronic books; Handbooks and manuals; Electronic books